Handbook of industrial and systems engineering - Badiru, Adedeji Bodunde, 1952- (Industrial innovation series., 2014)
"A new edition of the bestselling industrial and systems engineering text, this book provides students, researchers, and practitioners with easy access to a wide range of industrial engineering tools and techniques in a concise format. It expands the breadth and depth of coverage, emphasizing new systems engineering tools, techniques, and models. New coverage includes control charts, engineering economy, health operational efficiency, healthcare systems, human systems integration, lean systems, logistics transportation, manufacturing systems, material handling systems, process view of work, queuing systems, reliability systems and tools, and six sigma techniques"--